Ex vivo quantitative analysis of human corneal stroma dehydration by near‐infrared absorption spectroscopy. Issue 10 (1st July 2019) - Qi, Pengfei; Sun, Lu; Ma, Jiaonan; Yao, Jiali; Lin, Lie; Zhang, Lin; Wang, Yan; Liu, Weiwei
Abstract: Corneal water content and hydrodynamics are critical indicators of eye health. In this work, a convenient method based on near‐infrared absorption spectroscopy (NIRA) was presented to measure the relative water content of the corneal stroma ex vivo, which paves the way to measure corneal water content in vivo. The relative water content of fresh corneal stroma during dehydration under natural conditions (temperature, 25.8 ± 0.3°C; humidity, 7.2% ± 0.9%) was monitored in real time, and the characteristic time τ when the relative water content dropped to 90% of the fresh corneal stroma was 140.1 ± 30.6 s. Furthermore, the change in the relative water content over time was found to be linear with a dehydration rate of 0.071% per second, consistent with indirect optical coherence pachymetry but with superior reproducibility and precision. Provided that the NIRA spectrometer is changed to a reflection structure from the current transmission configuration, the NIRA method proposed in this work has great potential for in vivo measurement with the advantages of non‐contact, high precision and low cost. Abstract : A convenient method based on near‐infrared absorption spectroscopy (NIRA) was presented to measure the relative water content of ex vivo corneal stroma, which paves the way to measure water content of cornea in vivo. The relative water content of fresh corneal stroma during dehydration under natural conditions was monitored in real time. The result is consistent with indirect optical coherence pachymetry (OCP) but with superior reproducibility and precision.